Recursos educacionais abertos e direitos autorais em ambientes virtuais de aprendizagem: conflitos e perspectivas - Manole, Daniela (2014)
The key elements of this work emerge in an environment of an enormous use of web 2.0/3.0 for authorship together with a exponential growth of massive online educational initiatives with strong technology usage, where open educational resources with creative commons licenses and copyrighted materials oppose to materials without any indication of license, and at the same time there is a tension on the creative work of professors and students as to whom belongs its fruits. This research aims to analyze some of these environments where the conflicts are present, get to know the Bills of Law that tries to adjust to the new reality, in Brazil and elsewhere, as well as questioning and identify the key curriculum elements and pedagogical strategies used in the educational conceptualization of massive virtual environments. Through search one seeks comprehension of philosophical changes at todays cybernetic moment, trying to understand the need of change in teachers and students new roles. The problem is defined as the exposure of points of conflict between Open Educational Resources (OER) and copyrights in virtual learning environments, which in turn could comprehend a group of Learning Objects (LO), cited in various documents within this work. The results of this work suggests that in short and mid term learning objects which form the contents of a course kept in a virtual environment from a public or private institution, needs to be standardized and should explicitly contain, in metadata format, the kinds of embedded license whereas from copyrights or open educational resources under creative commons. The possibility of using LO with the appropriate and complete license information within metadata, depends on faculty knowledge for authorship as well as reuse of LO from another authors, so established principles can be applied